GRANÜLOSİT KOLONİ STİMÜLASYON FAKTÖR VE REKOMBİNANTI HUMAN ERİTROPOETİNİN DOKSORBİSİNE BAĞLI DERİ NEKROZU ÜZERİNE ETKİLERİ - ŞİMŞEKLİ, HÜSEYİN (Fırat Üniveristesi, 2005)
EFFECTS OF G-CSF AND HUMAN RECOMBINANT ERYTHROPOIETIN ON DOXORUBICIN INDUCED SKIN NECROSIS Extravasation of antineoplastic agents is an infrequent but significant side effect of chemotherapy. This local toxicity is characterised by pain, erythema and swelling at the extravasation site and can progress to tissue necrosis and ulceration. Extravasation of doxorubicin into the skin or subcutaneous tissues may result in loss of the full thickness the skin or underlying structures. Erythropoietin is a principal hematopoietic growth factor responsible for the proliferation and differentiation of erythroid progenitor cells. EPO plays an important role in regulating angiogenesis, in endothelial cell and myoblast proliferation, in cardiac morphogenesis and in neurogenesis. G-CSF is a glycoprotein growth factor, it has a predominant effect on granulocyte progenitors. G-CSF uses to the neutropenia associated with cytotoxic chemotherapy, bone marrow and hematopoietic stem cell transplantation. In this study, we used to investigate the local effect of EPO and G-CSF injections to a doxorubicin extravasation site. Twenty seven Wistar- Albino rats weighing 170-200 gr were used. All rats were injected with 1 mg doxorubicin intradermally in 0,5 ml SF. Group 1 (control, n=8): intradermal injection of 0,1 ml SF to the same site. Group 2 (EPO treatment, n=10): intradermal injection of 100 u/kg EPO to the same site. Group 3 (G-CSF treatmant, n=9): intradermal injection of 10 meg G-CSF to the same site. All injections were applied at every other day in ten days. On the tenth day after the doxorubicin injection the entire area of ulcerated skin together with the underlying structures was excised for each rats. Tissue hydroxyproline level, erythrocyte glocose 6 phosphate dehydrogenase level, other biochemical parameters such as liver function and renal function tests and histopathological findings were assessed. ALP levels were significantly increased in the G-CSF group than the control group (p<0.05). However, ALP levels of G-CSF group were significantly reduced than ALP levels of EPO group (p<0.05). There were no statistical significance in other parameters and2.ABSTRACT EFFECTS OF G-CSF AND HUMAN RECOMBINANT ERYTHROPOIETIN ON DOXORUBICIN INDUCED SKIN NECROSIS Extravasation of antineoplastic agents is an infrequent but significant side effect of chemotherapy. This local toxicity is characterised by pain, erythema and swelling at the extravasation site and can progress to tissue necrosis and ulceration. Extravasation of doxorubicin into the skin or subcutaneous tissues may result in loss of the full thickness the skin or underlying structures. Erythropoietin is a principal hematopoietic growth factor responsible for the proliferation and differentiation of erythroid progenitor cells. EPO plays an important role in regulating angiogenesis, in endothelial cell and myoblast proliferation, in cardiac morphogenesis and in neurogenesis. G-CSF is a glycoprotein growth factor, it has a predominant effect on granulocyte progenitors. G-CSF uses to the neutropenia associated with cytotoxic chemotherapy, bone marrow and hematopoietic stem cell transplantation. In this study, we used to investigate the local effect of EPO and G-CSF injections to a doxorubicin extravasation site. Twenty seven Wistar- Albino rats weighing 170-200 gr were used. All rats were injected with 1 mg doxorubicin intradermally in 0,5 ml SF. Group 1 (control, n=8): intradermal injection of 0,1 ml SF to the same site. Group 2 (EPO treatment, n=10): intradermal injection of 100 u/kg EPO to the same site. Group 3 (G-CSF treatmant, n=9): intradermal injection of 10 meg G-CSF to the same site. All injections were applied at every other day in ten days. On the tenth day after the doxorubicin injection the entire area of ulcerated skin together with the underlying structures was excised for each rats. Tissue hydroxyproline level, erythrocyte glocose 6 phosphate dehydrogenase level, other biochemical parameters such as liver function and renal function tests and histopathological findings were assessed. ALP levels were significantly increased in the G-CSF group than the control group (p<0.05). However, ALP levels of G-CSF group were significantly reduced than ALP levels of EPO group (p<0.05). There were no statistical significance in other parameters and

EFFECTS OF G-CSF AND HUMAN RECOMBINANT ERYTHROPOIETIN ON DOXORUBICIN INDUCED SKIN NECROSIS Extravasation of antineoplastic agents is an infrequent but significant side effect of chemotherapy. This local toxicity is characterised by pain, erythema and swelling at the extravasation site and can progress to tissue necrosis and ulceration. Extravasation of doxorubicin into the skin or subcutaneous tissues may result in loss of the full thickness the skin or underlying structures. Erythropoietin is a principal hematopoietic growth factor responsible for the proliferation and differentiation of erythroid progenitor cells. EPO plays an important role in regulating angiogenesis, in endothelial cell and myoblast proliferation, in cardiac morphogenesis and in neurogenesis. G-CSF is a glycoprotein growth factor, it has a predominant effect on granulocyte progenitors. G-CSF uses to the neutropenia associated with cytotoxic chemotherapy, bone marrow and hematopoietic stem cell transplantation. In this study, we used to investigate the local effect of EPO and G-CSF injections to a doxorubicin extravasation site. Twenty seven Wistar- Albino rats weighing 170-200 gr were used. All rats were injected with 1 mg doxorubicin intradermally in 0,5 ml SF. Group 1 (control, n=8): intradermal injection of 0,1 ml SF to the same site. Group 2 (EPO treatment, n=10): intradermal injection of 100 u/kg EPO to the same site. Group 3 (G-CSF treatmant, n=9): intradermal injection of 10 meg G-CSF to the same site. All injections were applied at every other day in ten days. On the tenth day after the doxorubicin injection the entire area of ulcerated skin together with the underlying structures was excised for each rats. Tissue hydroxyproline level, erythrocyte glocose 6 phosphate dehydrogenase level, other biochemical parameters such as liver function and renal function tests and histopathological findings were assessed. ALP levels were significantly increased in the G-CSF group than the control group (p<0.05). However, ALP levels of G-CSF group were significantly reduced than ALP levels of EPO group (p<0.05). There were no statistical significance in other parameters andEFFECTS OF G-CSF AND HUMAN RECOMBINANT ERYTHROPOIETIN ON DOXORUBICIN INDUCED SKIN NECROSIS Extravasation of antineoplastic agents is an infrequent but significant side effect of chemotherapy. This local toxicity is characterised by pain, erythema and swelling at the extravasation site and can progress to tissue necrosis and ulceration. Extravasation of doxorubicin into the skin or subcutaneous tissues may result in loss of the full thickness the skin or underlying structures. Erythropoietin is a principal hematopoietic growth factor responsible for the proliferation and differentiation of erythroid progenitor cells. EPO plays an important role in regulating angiogenesis, in endothelial cell and myoblast proliferation, in cardiac morphogenesis and in neurogenesis. G-CSF is a glycoprotein growth factor, it has a predominant effect on granulocyte progenitors. G-CSF uses to the neutropenia associated with cytotoxic chemotherapy, bone marrow and hematopoietic stem cell transplantation. In this study, we used to investigate the local effect of EPO and G-CSF injections to a doxorubicin extravasation site. Twenty seven Wistar- Albino rats weighing 170-200 gr were used. All rats were injected with 1 mg doxorubicin intradermally in 0,5 ml SF. Group 1 (control, n=8): intradermal injection of 0,1 ml SF to the same site. Group 2 (EPO treatment, n=10): intradermal injection of 100 u/kg EPO to the same site. Group 3 (G-CSF treatmant, n=9): intradermal injection of 10 meg G-CSF to the same site. All injections were applied at every other day in ten days. On the tenth day after the doxorubicin injection the entire area of ulcerated skin together with the underlying structures was excised for each rats. Tissue hydroxyproline level, erythrocyte glocose 6 phosphate dehydrogenase level, other biochemical parameters such as liver function and renal function tests and histopathological findings were assessed. ALP levels were significantly increased in the G-CSF group than the control group (p<0.05). However, ALP levels of G-CSF group were significantly reduced than ALP levels of EPO group (p<0.05). There were no statistical significance in other parameters and
Effects of G-CFS and human recombinant erythropoietin on doxorubicin induced skin necrsis
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz.
Keywords: Nefroloji